2012
DOI: 10.3390/nu4111767
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Diets Supplemented with Branched-Chain Amino Acids on the Performance and Fatigue Mechanisms of Rats Submitted to Prolonged Physical Exercise

Abstract: This study aimed to determine the effects of diets chronically supplemented with branched-chain amino acids (BCAA) on the fatigue mechanisms of trained rats. Thirty-six adult Wistar rats were trained for six weeks. The training protocol consisted of bouts of swimming exercise (one hour a day, five times a week, for six weeks). The animals received a control diet (C) (n = 12), a diet supplemented with 3.57% BCAA (S1) (n = 12), or a diet supplemented with 4.76% BCAA (S2) (n = 12). On the last day of the training… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 39 publications
2
46
0
Order By: Relevance
“…[44][45][46] BCAA are also related to central fatigue delay and the reduction of hepatic encephalopathy symptoms, by decreasing influx of sulfonated amino acids through the blood-brain barrier. [47][48][49] Oxidation of BCAA by the liver As previously mentioned, the liver shows an absence or low activity of BCAT and as a result, unlike other amino acids, BCAA are not primarily catabolized in this organ.…”
Section: Oxidation Of Bcaa By the Brainmentioning
confidence: 89%
“…[44][45][46] BCAA are also related to central fatigue delay and the reduction of hepatic encephalopathy symptoms, by decreasing influx of sulfonated amino acids through the blood-brain barrier. [47][48][49] Oxidation of BCAA by the liver As previously mentioned, the liver shows an absence or low activity of BCAT and as a result, unlike other amino acids, BCAA are not primarily catabolized in this organ.…”
Section: Oxidation Of Bcaa By the Brainmentioning
confidence: 89%
“…The increased glycogen accumulation in the liver and skeletal muscles has been suggested to improve physical endurance [9,10]. Gina et al also showed that rats have high contents in the soleus muscle, which indicates strong resistance from swim exhaustion [11]. Aspalathin present in rooibos has also been shown to increase glucose intake via the up-regulation of GLUT4 translocation to the cell membrane [4][5][6], which may stimulate glycogen accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…A high-protein diet would cause hyperammonemia, and ammonia has been reported to cause deterioration of mitochondria through the production of reactive oxygen species (1,29), and it has been known to provoke central and peripheral fatigue (14) and would alter energy consumption. Fumarate, which is a degradation product of protein and amino acids, has been reported to cause impairment of muscle contractility (21) and fatigue (20).…”
Section: Discussionmentioning
confidence: 99%